Effect of increasing vertical centre of mass displacement on the biomechanical stimulus of traditional resistance training exercises - Swinton, P.; Agouris, I.; Lloyd, R.; Stewart, A.; Keogh, J. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
This study investigated the effect of systematically increasing vertical COM displacement on the biomechanical stimulus of a traditional resistance training exercise. Fourteen male rugby union athletes performed maximum velocity repetitions of the deadlift to four different final vertical positions with external loads of 20, 40 and 60% 1RM. Significant increases in force, velocity and power were obtained with lifting techniques that resulted in greater vertical COM displacement, although significant interaction effects revealed that improvements were attenuated with heavier loads. These results have applications to strength and conditioning practice, whereby the traditional resistance training exercise stimulus can be augmented without imposing the overly large eccentric musculoskeletal loads characteristic of landing from maximal weighted vertical jumps.